The Impact of Social Media and Digital Marketing on Consumer Preferences for Organic Vegetables - Alfakihuddin, Muhammad Lukman Baihaqi; Jayaputra, Trimardi; Arthawati, Sri Ndaru; Oktavera, Rini; Ovrillia Praditha, Muhril Ardiansyah, (SEIKO : Journal of Management & Business, 2024)
The consumption of organic veggies has undergone a tremendous growth in recent years. Digital marketing and social media have developed as powerful channels for content transmission and consumer involvement. Despite the growing trend for organic veggies, there remains a limited understanding of how digital marketing and social media influence customer choices in this industry. The research purpose to identify the impact of digital marketing and social media on the choices and preferences of customers in the organic vegetable industry. This research employs a quantitative method. The sample comprised of 69 people who buy organic veggies in the city of Malang. The questionnaire was shared through Facebook groups. The selection of respondents was based on a non-probability sampling technique, specifically convenience sampling. F-test results reveal that Digital Marketing and Social Media greatly influence Consumer Preference. The R-Squared value of 0.956 suggests that 95.6% of the variance in Consumer Preferences can be explained by Digital Marketing and Social Media. T-test results, Social Media has a considerable influence on Consumer Preferences. Digital Marketing does not greatly affect Consumer Preferences. Digital Marketing and Social Media collectively influence Consumer Preferences, with 95.6% of the variation being explained by these factors; yet, while Social Media has a large impact, Digital Marketing does not. Kata Kunci: Impact, Social Media, Digital Marketing, Consumer Preferences, Organic Vegetables